2016
DOI: 10.1016/j.mee.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost top-down zinc oxide nanowire sensors through a highly transferable ion beam etching for healthcare applications

Abstract: Abstract-In this work, we demonstrate a wafer-level zinc oxide (ZnO) nanowire fabrication process using ion beam etching and a spacer etch technique. The proposed process can accurately define nanowires without an advanced photolithography and provide a high yield over a 6-inch wafer. The fabricated nanowires are 36 nm wide and 86 nm thick and present excellent transistor characteristics. The pH sensitivity using a liquid gate was found to be 46.5 mV/pH, while the pH sensitivity using a bottom gate showed a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Although this enables the deposition of highly conductive films, high-quality ZnO films are difficult to obtain with low carrier concentration. The plasma-enhanced ALD is preferably used when low-carrier concentration ZnO is required [ 19 , 20 ]. We recently reported the capability of tuning ZnO using a single plasma-enhanced ALD process which allows the tuning of its resistivity and carrier concentration up to three orders by using different O 2 plasma times [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this enables the deposition of highly conductive films, high-quality ZnO films are difficult to obtain with low carrier concentration. The plasma-enhanced ALD is preferably used when low-carrier concentration ZnO is required [ 19 , 20 ]. We recently reported the capability of tuning ZnO using a single plasma-enhanced ALD process which allows the tuning of its resistivity and carrier concentration up to three orders by using different O 2 plasma times [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…7). 57 On the other hand, some other technologies, such as nanowire biosensors, present great potential for the quantitation of protein biomarkers at POC settings, as these can be cost-effective 133 and allow sensitive detection without labels. 134,135 It has been shown that silicon nanowires with a primary antibody covalently bound to their surface enable the detection of biomarkers by registering a change in the conductance, which is proportional to the amount of antigen bound.…”
Section: View Article Onlinementioning
confidence: 99%
“…In the latter case, the device is called GAA FET. Another option is to grow the NWs vertically using, for example, conformal chemical vapor deposition [54], dry etching with reduced oxidation techniques [55], or ion beam etching and the spacer etch technique presented in [56].…”
Section: Nanowires and 3-d Stackingmentioning
confidence: 99%